MODEL PJBL BERBANTUAN POP-UP BOOK INTEGRASI BUDAYA LOKAL MADURA ROKAT TASE’ UNTUK MENINGKATKAN KREATIVITAS IPAS - Andika Adinanda Siswoyo; Rifka Aidah Fatin; Ade Irma Damayanti; Sri Wilda Ningsih; Zafirah Rifatil Badri (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
This classroom action research (CAR) is motivated by the critical need for conceptual media innovations to stimulate fine motor skills and socio-cultural comprehension among primary school students who tend to remain passive. This study aims to enhance the psychomotor skills and creative thinking of fourth-grade students at SDN Tanjung Jati 2 Bangkalan in Science and Social Studies (IPAS) learning through the implementation of the Project-Based Learning (PjBL) model assisted by Pop-up book media themed around the local wisdom of the Rokat Tase’ tradition. The research methodology follows the Kemmis & McTaggart spiral model conducted across two action cycles, comprising planning, acting, observing, and reflecting stages with 15 students as research subjects. Data collection was comprehensively carried out using activity observation sheets, a product assessment rubric based on four core aspects of creativity, student worksheets (LKPD), and student response questionnaires. The findings revealed a notable improvement in the quality of students’ products from Cycle I to Cycle II across various dimensions of creativity. The most substantial progress was observed in originality and elaboration, while fluency and flexibility consistently demonstrated high levels of achievement. Improvements in product quality were also accompanied by enhanced sociocultural literacy skills, higher cognitive learning outcomes, and highly positive student responses to the learning process. These findings suggest that instructional practices supported by individualized scaffolding can effectively foster students’ creativity and optimize their learning outcomes. In conclusion, the integration of the geographical context of the Pantai Batu Poron area into the PjBL model is proven reliable in boosting individual creative capacity and academic comprehension meaningfully, allowing the classroom action to be successfully concluded. ABSTRAK Penelitian tindakan kelas (PTK) ini dilatarbelakangi oleh perlunya inovasi media konseptual untuk menstimulus kreativitas motorik halus dan pemahaman sosiokultural siswa sekolah dasar yang cenderung masih pasif. Penelitian ini bertujuan untuk meningkatkan keterampilan psikomotorik dan berpikir kreatif siswa kelas IV SDN Tanjung Jati 2 Bangkalan dalam pembelajaran IPAS melalui penerapan model Project-Based Learning (PjBL) berbantuan media Pop-up book bertema kearifan lokal tradisi Rokat Tase’. Metode penelitian dirancang mengikuti model spiral Kemmis & McTaggart yang dilaksanakan dalam dua siklus tindakan, meliputi tahapan perencanaan, pelaksanaan, pengamatan, dan refleksi dengan subjek penelitian sebanyak 15 siswa. Pengumpulan data dilakukan secara komprehensif menggunakan lembar observasi aktivitas, rubrik penilaian produk berbasis empat aspek utama kreativitas, Lembar Kerja Peserta Didik (LKPD), serta angket respon siswa. Hasil penelitian menunjukkan adanya peningkatan kualitas produk karya siswa dari Siklus I ke Siklus II pada berbagai aspek kreativitas. Perkembangan paling menonjol terlihat pada aspek keaslian dan perincian ide, sementara aspek kelancaran dan keluwesan tetap menunjukkan capaian yang tinggi. Peningkatan kualitas produk siswa juga diikuti oleh perkembangan kemampuan literasi sosiokultural, hasil belajar kognitif, dan respons belajar yang sangat positif. Temuan ini menunjukkan bahwa penerapan pembelajaran yang disertai bimbingan personal mampu mendukung pengembangan kreativitas dan meningkatkan hasil belajar siswa secara optimal. Disimpulkan bahwa integrasi konteks geografis wilayah Pantai Batu Poron ke dalam model PjBL terbukti andal dalam melejitkan daya cipta individual serta pemahaman akademis siswa secara bermakna, sehingga tindakan kelas dihentikan secara tuntas.